ST3Gal.I sialyltransferase relevance in bladder cancer tissues and cell lines - Videira, Paula A; Correia, Manuela; Malagolini, Nadia; Crespo, Hélio J; Ligeiro, Dário; Calais, Fernando M; Trindade, Helder; Dall'Olio, Fabio (BMC cancer, 2009)
The T antigen is a tumor-associated structure whose sialylated form (the sialyl-T antigen) involves the altered expression of sialyltransferases and has been related with worse prognosis. Since little or no information is available on this subject, we investigated the regulation of the sialyltransferases, able to sialylate the T antigen, in bladder cancer progression. Matched samples of urothelium and tumor tissue, and four bladder cancer cell lines were screened for: ST3Gal.I, ST3Gal.II and ST3Gal.IV mRNA level by real-time PCR. Sialyl-T antigen was detected by dot blot and flow cytometry using peanut lectin. Sialyltransferase activity was measured against the T antigen in the cell lines. In nonmuscle-invasive bladder cancers, ST3Gal.I mRNA levels were significantly higher than corresponding urothelium (p < 0.001) and this increase was twice more pronounced in cancers with tendency for recurrence. In muscle-invasive cancers and matching urothelium, ST3Gal.I mRNA levels were as elevated as nonmuscle-invasive cancers. Both non-malignant bladder tumors and corresponding urothelium showed ST3Gal.I mRNA levels lower than all the other specimen groups. A good correlation was observed in bladder cancer cell lines between the ST3Gal.I mRNA level, the ST activity (r = 0.99; p = 0.001) and sialyl-T antigen expression, demonstrating that sialylation of T antigen is attributable to ST3Gal.I. The expression of sialyl-T antigens was found in patients' bladder tumors and urothelium, although without a marked relationship with mRNA level. The two ST3Gal.I transcript variants were also equally expressed, independently of cell phenotype or malignancy. ST3Gal.I plays the major role in the sialylation of the T antigen in bladder cancer. The overexpression of ST3Gal.I seems to be part of the initial oncogenic transformation of bladder and can be considered when predicting cancer progression and recurrence.